Phylogeographic characterization of scorpions of the genus Mesobuthus Vachon, 1950 - Poverenniy, Nikita M.; Anikin, Vasilii V. (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология)
The study of zoogeographic characteristics in combination with the use of modern methods for assessing phylogenetic relationships allowed us to examine in detail the phylogeographic structure in scorpions of the genus Mesobuthus. In this work, to assess phylogenetic relationships, we used the decoded sequences of the COI gene fragment obtained by the team of authors in collaborative work and deposited in the Genbank database (NCBI). Previously published results of zoogeographic studies, due to the lack of data on the distribution of species of this genus, did not fully refl ect the zoogeographic structure of the genus Mesobuthus. Therefore, the previously typifi ed ranges of some species of the genus Mesobuthus were revised in this work. For this purpose, specimens from the collection of the Zoological Institute of the Russian Academy of Sciences were studied. To establish the zoogeographic position of the genus Mesobuthus, the biogeographic zoning of the Palaearctic, proposed by Emelyanov A. F. and Krivokhatsky V. A., was chosen. According to the results of the study, fi ve species groups (phillipsii, kirmanensis, eupeus, afghanus, thersites) were identifi ed in the genus Mesobuthus using phylogenetic analysis. The zoogeographic analysis identifi ed two clusters consisting of eight elemental faunas. In addition, transition zones between the North Central Asian and Iranian-Mekranian elemental faunas, as well as between the Khorasan-Girkan and South Turkana-Afghan elemental faunas were identifi ed. In this study, based on the dates obtained, it was found that in scorpions of the genus Mesobuthus, the hypothetical center of origin coincides with the modern chorological center, which is the Iranian-Mekranian elemental fauna. Phylogenetic relationships between fi ve groups of species prove that the genus Mesobuthus spread from the Iranian-Mekranian elemental fauna to the north, forming the other elemental faunas. Also, it is established that the main processes of Mesobuthus genus faunagenesis fall on the period from the middle Miocene to the late Pliocene.